The seasonal cycle of Titan's detached haze. (June 2018) - West, Robert; Seignovert, Benoît; Rannou, Pascal; Dumont, Philip; Turtle, Elizabeth; Perry, Jason; Roy, Mou; Ovanessian, Aida
Abstract Titan's 'detached' haze, seen in Voyager images in 1980 and 1981 and monitored by the Cassini Imaging Science Subsystem (ISS) during the period 2004–2017, provides a measure of seasonal activity in Titan's mesosphere with observations over almost half of Saturn's seasonal cycle. Here we report on retrieved haze extinction profiles that reveal a depleted layer (having a diminished aerosol content), visually manifested as a gap between the main haze and a thin, detached upper layer. Our measurements show the disappearance of the feature in 2012 and its reappearance in 2016, as well as details after the reappearance. These observations highlight the dynamical nature of the detached haze. The reappearance seems congruent with earlier descriptions by climate models but more complex than previously described. It occurs in two steps, first as haze reappearing at 450 ± 20 km and one year later at 510 ± 20 km. These observations provide additional tight and valuable constraints about the underlying mechanisms, especially for Titan's mesosphere, that control Titan's haze cycle. Titan's detached haze, a distinct layer on top of the main haze that provides a measure of the seasonal activity in the mesosphere, disappeared from 2012–2016, after equinox. Studying this transition will help us understand the dynamical and microphysical processes at work.